553 Does Patella Implant Design Affect Outcomes? Patella Resurfacing in Total Knee Arthroplasty: A Systematic Review and Meta-Analysis. (19th August 2022) - Yap, NJ; Simpson, C; Ng, N; Ndou, S; Wright, E; Scott, C; Clement, N
Abstract: Aim: To investigate whether implant design affect (1)incidence of anterior knee pain, (2)patient reported outcomes and (3)reintervention rates in a resurfaced vs non-resurfaced Total Knee Arthroplasty (TKA). Method: MEDline, pubmed and google scholar studies were evaluated using SIGN assessment tool and data analysis was conducted using Review Manager 5.2 on only randomised controlled trials. Search terms: arthroplasty, replacement, knee (Mesh), TKA, prosthesis, patella, patellar resurfacing, patellar retaining. Results: 33 randomised controlled studies were identified. A total of 11 used the modern "patella-friendly" implants and 22 used the older "patella non-friendly" implants. There was no significant difference in anterior knee pain rates for either surgical option. When using patella-friendly implant, patella resurfacing results in a statistically higher clinical (P 0.007, MD -0.77) and functional (P < 0.0001, MD -1.87) KSS than the non-resurfaced counterparts, but scores were not clinically significant. When the patella was not resurfaced, there was a significant increased risk of reoperation with "non-patella friendly" implant (p=0.04, OR 1.42, CI 1.01, 2.00), whilst there was no significant difference between reoperation rates for the "patella friendly" implants (OR 1.17, CI 0.59, 2.30). Conclusions: Patella implant design has been shown to significantly improve KSS scores but with no clinical significance. Risk of further procedures was significantly higher in non-resurfaced patella TKAs with "non-friendly" implants, likely due to increased rates of anterior knee pain in these older generation implants leading to secondary resurfacing. However, when utilising "patella-friendly" implants, resurfacing does not lower reintervention rates. This meta-analysis finds no clinical indication to resurface the patellar whilst performing a TKA.